Peran Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Ciamis Dalam Penerbitan Nomor Induk Berusaha Melalui Sistem OSS - Maha Shania Tara Gusmoi; Asep Nurwanda; Arie Budiawan (Faculty of Social and Political Science, 2024)
This study aims to describe the role of the Ciamis Regency Investment and One-Stop Integrated Service Office (DPMPTSP) as a facilitator of business legality through the implementation of the Online Single Submission (OSS) system, especially in the issuance of Business Identification Numbers (NIB). The background of this study is based on the importance of business legality for MSMEs to increase access to financing, legal protection, and market development. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the Ciamis Regency DPMPTSP has made efforts as a facilitator quite optimally, especially in providing technical assistance, socializing the OSS system, and assisting business actors in the registration process until the issuance of the NIB. However, there are several obstacles such as limited human resources for business actors, lack of digital literacy, and limited network infrastructure in certain areas. The active role of DPMPTSP in bridging central government policies with community needs is the key to the successful implementation of the OSS system in the region. Therefore, it is necessary to strengthen institutional capacity and a more effective communication strategy to increase the participation of business actors in the legalization of their businesses.